Solanum torvum for hypertension in ‘Kitab al Tibb’: A systematic review on the scientific evidence - Ismail, Azlini (2021)
This PDF contains 33-pages of slides which has been presented by the inventor while participating in the International Conference on Malay Medical Manuscripts, from 15th-16th December 2020